1997
DOI: 10.1161/01.res.81.4.493
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1β Inhibits Phospholamban Gene Expression in Cultured Cardiomyocytes

Abstract: Phospholamban is a key regulatory protein that defines diastolic function. Proinflammatory cytokines interleukin-1 beta (IL-1 beta) and tumor necrosis factor-alpha (TNF-alpha) can depress contractility and intracellular Ca2+ currents and transients. An alteration in phospholamban expression is a possible pathway by which these cytokines modulate cardiac function. To test this hypothesis, primary cultures of neonatal rat cardiomyocytes were incubated with IL-1 beta, TNF-alpha, or both, and the level of phosphol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
58
0
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 87 publications
(64 citation statements)
references
References 65 publications
5
58
0
1
Order By: Relevance
“…Moreover, IL-10 induces protection against myocardial injury by preventing apoptosis through the reduced phosphorylation of p38MAPK and the enhanced phosphorylation of STAT3 [42]. TNF-α and IL-1β promotes apoptosis in cardiac myocytes [43,44], which is also inhibited by IL-10. In the present study, we demonstrated that αGC administration ameliorated myocardial I/R injury (Figure 3) with upregulating serum and myocardial IL-10 ( Figure 6).…”
Section: Protective Effects Of Il-10 On Myocardial I/r Injurymentioning
confidence: 99%
“…Moreover, IL-10 induces protection against myocardial injury by preventing apoptosis through the reduced phosphorylation of p38MAPK and the enhanced phosphorylation of STAT3 [42]. TNF-α and IL-1β promotes apoptosis in cardiac myocytes [43,44], which is also inhibited by IL-10. In the present study, we demonstrated that αGC administration ameliorated myocardial I/R injury (Figure 3) with upregulating serum and myocardial IL-10 ( Figure 6).…”
Section: Protective Effects Of Il-10 On Myocardial I/r Injurymentioning
confidence: 99%
“…ulate the gene expression of multiple ion channels and proteins (15,17,35,36); we therefore examined whether IL-1␤ could alter gene expression of Ca V 1.2. The qPCR results shown in Fig.…”
Section: Il-1␤ Reduces the Density Of Imentioning
confidence: 99%
“…15,21 Neonatal cardiomyocytes were prepared as described above, plated onto glass coverslips, and cultured in the presence of LPS (E coli 0127, 100 ng/mL), LPS and adenosine (10 mol/L), or diluent for 4 days. Treatments were performed after isolation and repeated on days 2 and 4.…”
Section: Analysis Of Cytosolic Calcium and Contraction/relaxation Inmentioning
confidence: 99%